2008
DOI: 10.1080/10715760802311187
|View full text |Cite
|
Sign up to set email alerts
|

RNA oxidation: A contributing factor or an epiphenomenon in the process of neurodegeneration

Abstract: In the past decade, RNA oxidation has caught the attention of many researchers, working to uncover its role in the pathogenesis of neurodegenerative diseases. It has been well documented that RNA oxidation is involved in a wide variety of neurological diseases and is an early event in the process of neurodegeneration. The analysis of oxidized RNA species revealed that at least messenger RNA (mRNA) and ribosomal RNA (rRNA) are damaged in several neurodegenerative diseases, including Alzheimer's disease and amyo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 34 publications
0
19
0
Order By: Relevance
“…In addition, nucleic acid oxidation has been suggested to be a potential factor in cell loss in neurodegenerative diseases like amyotrophic lateral sclerosis (ALS) and Alzheimer’s disease (Nunomura et al, 1999; Shan et al, 2003; Chang et al, 2008; Kong et al, 2008). We therefore examined nucleic acid oxidation as a marker for oxidative stress in both the rhizotomy and contusion models.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, nucleic acid oxidation has been suggested to be a potential factor in cell loss in neurodegenerative diseases like amyotrophic lateral sclerosis (ALS) and Alzheimer’s disease (Nunomura et al, 1999; Shan et al, 2003; Chang et al, 2008; Kong et al, 2008). We therefore examined nucleic acid oxidation as a marker for oxidative stress in both the rhizotomy and contusion models.…”
Section: Resultsmentioning
confidence: 99%
“…26,27 Recent proteomic studies have identified many downregulated proteins in the postmortem brain tissue of patients with major depressive disorder, bipolar disorder and schizophrenia. [28][29][30][31] It will be interesting to determine whether RNA oxidative damage contributes to the downregulation of these proteins.…”
Section: Discussionmentioning
confidence: 99%
“…It is currently known that ribosomal and messenger RNA can be oxidized, and RNA-bound iron is also oxidized by the Fenton reaction (Honda et al 2005). Noncoding RNA species, such as transfer RNAs, microRNAs, and small nuclear and nucleolar RNAs, are also susceptible to oxidation (Kong et al 2008;Jacob et al 2013). The known molecular consequences of RNA oxidation are premature termination of reverse transcription, ribosomal dysfunction, aberrant and reduced protein synthesis, and translation of truncated or mutated proteins that are nonfunctional or prone to misfolding or aggregation (Rhee et al 1995;van Leeuwen et al 1998;Tanaka et al 2007;).…”
Section: Biomarkers Of Dna and Rna As Targets Of Oxidation Nucleotidementioning
confidence: 99%